Existence and Uniqueness of the Cauchy Problem for a Generalized Navier-Stokes Equations (Journal of Partial Differential Equations, 2003)
" We consider the Cauchy problem for a generalized Navier-Stokes equations with hyperdissipation, with the initial data in L^p_\u03c3. We follow the theme of [1] but with more complicated analysis on the symbol and obtain the existence and uniqueness results."